Effects of nitrogen application on growth and yield of maize. Issue 5 (September 2019) - Han, Xiaonan; Han, Nana; Zhou, Qingyun; Kang, Jie; Bai, Xinyan
Abstract: The effects of different nitrogen application levels on growth, dry matter accumulation, SPAD value, leaf area index and yield of maize were studied to provide theoretical basis for rational and efficient nitrogen application management of crops. In the field experiment, 225, 337.5, 450, and 675 kg ·hm −2 nitrogen application levels were set, respectively expressed by N1, N2, N3, and N4 . N0 without nitrogen fertilizer was used for the control experiment. During the growing period, plant height, leaf area index and SPAD were observed, and dry matter accumulation, yield and yield components were counted. The growth index, dry matter accumulation, yield and yield components of maize were influenced by different fertilization levels. When the nitrogen application amount is greater than 225 kg · hm −2, it could significantly promote the growth and development of corn and increase the yield. Through comparative analysis, it was concluded that when the nitrogen application amount was 280kg·hm −2, it was the optimal nitrogen application amount for the efficient production of corn in the experimental area.